Forme evanescenti di estetica urbana. William Kentridge a Roma - Patella, Giuseppe (Aesthetica Preprint, 2023)
The paper aims at discussing the topic of urban aesthetics through the case study of a particular contemporary artwork, by analysing from an aesthetic point of view the exemplary case of a huge site-specific artwork realized in Rome by the south African artist William Kentridge. Created in 2016 along the banks of the Tiber River in Rome, Triumphs and Laments is an artwork destined to disappear over time, and already almost disappeared. In the fragility and transiency of its forms, this kind of public art plays not only on the fragile nature of its materials, organic, alive, and therefore destined to perish, but also on the precariousness of the sense of historical memory and the need for its continuous activation. The extraordinary strength of this example of public art is then connected to the awareness of its impermanence and the activation of visual memory processes shared by all of us.